n = 1 ∑ 9 9 9 9 ( n + n + 1 ) ( 4 n + 4 n + 1 ) 1 = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
This is a classic example from Telescoping Series problem.
It can be easily seen that the given expression can be quite simplified if we multiply numerator and denominator by 4 n + 1 − 4 n .
Doing this we get:- n = 1 ∑ 9 9 9 9 ( 4 n + 1 − 4 n ) ( 4 n + 1 + 4 n ) ( n + 1 + n ) 4 n + 1 − 4 n = n = 1 ∑ 9 9 9 9 ( n + 1 − n ) ( n + 1 + n ) 4 n + 1 − 4 n = n = 1 ∑ 9 9 9 9 n + 1 − n 4 n + 1 − 4 n = n = 1 ∑ 9 9 9 9 4 n + 1 − 4 n = 4 2 − 1 + 4 3 − 4 2 + … 4 1 0 0 0 0 − 4 9 9 9 9 = − 1 + 1 0 = 9